Addressing the Problems Faced by Married International Students - Siti Nor Yaacob, Elham Vaez Rumaya Juhari (Universitas Ahmad Dahlan, 2015)
AbstractÂ In recent decade, there has been an increasing rate of international students all over the world, but little is known about the marital life of this population. The need to understand graduate studentsâ intentions to pursue an academic career has become more important over the years. While International studentsâ cross-cultural adjustment has received considerable attention in the sojourner literature, there is a paucity of research that addresses the unique challenges faced by the married international students. Therefore, this study attempts to examine the empirical findings of various studies that explore factors which contribute to problems of married international students, and have an integrated perspective on the problems that this population faces during their study. The results revealed that acculturation stress, financial stress and social support are the utmost problems that international couples experience. This study offers suggestions for universities to provide facilities that would decrease international studentsâ marital problems; also to prepare workshops to increase couplesâ knowledge of different conflict resolution methods which would be helpful to avoid conflict during their study abroad.Â Keywords: marital relationship, international students, socio cultural adjustment, academic problem